A baseline soil survey of two peatlands associated with a lithium-rich salt flat in the argentine puna: Physico-chemical characteristics, carbon storage and biota - Chiappero, María Fernanda (2021)
High-elevation peatlands are valuable because of their capacity to store high quantities of carbon (C) in their soils, but they are also vulnerable to disturbance caused by human activity. In the High Andean plateau, lithium mining is a growing industry that could have an unknown impact on peatlands associated with the lithium-rich salt flats under exploitation. We assessed different abiotic and biotic soil characteristics of the Laguna Negra (LN) and Laguna Tres Quebradas (LTQ) peatlands in the Argentine Puna, both of which may imminently be affected by lithium mining. We measured soil physico-chemical properties, soil C stocks, and soil microorganisms and mesofauna. Soils of the LN peatland stored four times more C and had significantly higher organic matter content, electrical conductivity and cation exchange capacity, but lower nitrate concentration, than soils of the LTQ peatland. The composition and abundance of soil microbial communities, determined by the phospholipid fatty acid (PLFA) method, were similar in the two peatlands. However, mesofauna communities were more abundant and diverse in LTQ than in LN. Our results show that each peatland has its own peculiar characteristics and could, therefore, differ from the other in function and response to disturbance originating from nearby lithium mining. This initial evaluation of peatland soils associated with salt flats in the Puna region represents a first step towards understanding the soil ecology of these ecosystems, and highlights the need for (and the importance of) baseline surveys where lithium extraction is in prospect.